Contribution of Student Level of Understanding in The Concept of Calculated Operations And Their Relationship to Set Operations - Charles Elbinus Barutu (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2021)
The problem in this study is: whether there is a contribution to the level of understanding of the concept of calculated operations against the operation of the association in students of SMP Negeri 1 Balikpapan. This study aims to find out if there is a contribution to the level of understanding of the concept of calculated operations against the operation of the association in students of SMP Negeri 1 Balikpapan. The population of this study is all students of grade VII-A SMP Negeri 1 Balikpapan consisting of 34 students. And as a sample in this study is the whole student. The data analysis technique used is to use non-premetric statistics